The perceived quality of interprofessional teamwork in an intensive care unit: A single centre intervention study. Issue 3 (3rd May 2016) - Van den Bulcke, Bo; Vyt, Andre; Vanheule, Stijn; Hoste, Eric; Decruyenaere, Johan; Benoit, Dominique
ABSTRACT: This article describes a study that evaluated the quality of teamwork in a surgical intensive care unit and assessed whether teamwork could be improved significantly through a tailor-made intervention. The quality of teamwork prior to and after the intervention was assessed using the Interprofessional Practice and Education Quality Scales (IPEQS) using the PROSE online diagnostics and documenting system, which assesses three domains of teamwork: organisational factors, care processes, and team members' attitudes and beliefs. Furthermore, team members evaluated strengths and weaknesses of the teamwork through open-ended questions. Information gathered by means of the open questions was used to design a tailor-made 12-week intervention consisting of (1) optimising the existing weekly interdisciplinary meetings with collaborative decision-making and clear communication of goal-oriented actions, including the psychosocial aspects of care; and (2) organising and supporting the effective exchange of information over time between all professions involved. It was found that the intervention had a significant impact on organisational factors and care processes related to interprofessional teamwork for the total group and within all subgroups, despite baseline differences between the subgroups in interprofessional teamwork. In conclusion, teamwork, and more particularly the organisational aspects of interprofessional collaboration and processes of care, can be improved by a tailor-made intervention that takes into account the professional needs of healthcare workers.